2007
DOI: 10.1016/j.eurpsy.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Insular cortex and neuropsychiatric disorders: A review of recent literature

Abstract: The insular cortex is located in the centre of the cerebral hemisphere, having connections with the primary and secondary somatosensory areas, anterior cingulate cortex, amygdaloid body, prefrontal cortex, superior temporal gyrus, temporal pole, orbitofrontal cortex, frontal and parietal opercula, primary and association auditory cortices, visual association cortex, olfactory bulb, hippocampus, entorhinal cortex, and motor cortex. Accordingly, dense connections exist among insular cortex neurons. The insular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
202
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(218 citation statements)
references
References 74 publications
12
202
2
2
Order By: Relevance
“…The insula is involved in gustatory, visceral sensation and visceral motor responses, but also in psychosomatic functions with autonomic regulation and emotion processing (see Damasio et al, 2000, Ketter et al,1996, Reiman et al, 1989Lane et al, 1997;Ottowitz et al, 2004; for an overview, see Nagai et al, 2007). Mayberg et al (1999) and Kennedy et al (2001) found post-treatment responsiveness associated with decreased metabolism in the insula.…”
Section: Discussionmentioning
confidence: 99%
“…The insula is involved in gustatory, visceral sensation and visceral motor responses, but also in psychosomatic functions with autonomic regulation and emotion processing (see Damasio et al, 2000, Ketter et al,1996, Reiman et al, 1989Lane et al, 1997;Ottowitz et al, 2004; for an overview, see Nagai et al, 2007). Mayberg et al (1999) and Kennedy et al (2001) found post-treatment responsiveness associated with decreased metabolism in the insula.…”
Section: Discussionmentioning
confidence: 99%
“…The insular cortex has been associated with a variety of different functions, such as cognitive control (Cole and Schneider, 2007), individual emotions (Nieuwenhuys, 2012;Phan et al, 2002), and social emotion, including empathy and compassion, as well as interpersonal phenomena such as fairness and cooperation (Lamm and Singer, 2010). Also, the importance of the insular cortex has already been shown in several diseases associated with social-cognitive dysfunction such as mood disorders, post-stroke depression, panic disorders, post-traumatic stress disorders, obsessive compulsive disorder, and schizophrenia (Nagai et al, 2007). Hence, a shift in functional connectivity of the …”
Section: Discussionmentioning
confidence: 99%
“…9 The insula is involved in emotional arousal and visceral sensory, autonomic visceral motor, and pain processing 33 and is consistently activated in healthy subjects exposed to visceral stimuli. 6 The insula is also an essential node in the homeostatic afferent network that is hyperactivated in IBS.…”
Section: Higher Amygdala-insula Rsfc In Ibsmentioning
confidence: 99%